Relative signal intensity on time-of-flight magnetic resonance angiography as a novel indicator of aggressive presentation of intracranial dural arteriovenous fistulas - Ryu, Bikei (J Cereb Blood Flow Metab, 2020)
Asymptomatic dural arteriovenous fistulas (DAVFs) with cortical venous reflux (CVR) are now more commonly encountered. However, patients with an incidental onset may have a less aggressive clinical course. It is desirable to explore methods and indicators to predict the clinical outcomes. This study investigates whether the relative signal intensity (rSI) of the draining vessels on the time-of-flight magnetic resonance angiography is related to clinical behavior in patients with intracranial DAVFs. We retrospectively reviewed 36 intracranial DAVFs. The patients were categorized as those with either aggressive-presentation or non-aggressive-presentation (n = 16 and 20, respectively). The rSIs of the shunt points, affected sinuses, and veins with CVR were compared between the two groups. The two groups were not significantly different in terms of rSIs of the shunt points and affected sinuses (p = 0.37 and 0.41, respectively). However, a significant positive correlation was observed in the rSI of the veins with CVR between the aggressive and non-aggressive behavior groups (p < 0.0001). The rSI of the veins with CVR could serve as a reliable indicator of aggressive behavior in intracranial DAVFs, and its optimal cutoff value was 1.63 with high sensitivity and specificity for predicting aggressive behavior (area under the curve, 0.909).